Parathyroid hormone therapy improves MRSA-infected fracture healing in a murine diabetic model - Kwon, Hyuk-Kwon; Cahill, Sean V.; Yu, Kristin E.; Alder, Kareme D.; Dussik, Christopher M.; Jeong, Jain; Back, Jung Ho; Lee, Francis Y. (Frontiers in Cellular and Infection Microbiology, 2023)
Diabetes mellitus (DM) impairs fracture healing and is associated with susceptibility to infection, which further inhibits fracture healing. While intermittent parathyroid hormone (1-34) (iPTH) effectively improves fracture healing, it is unknown whether infection-associated impaired fracture healing can be rescued with PTH. A chronic, diet-induced Type 2 diabetic mouse model was used to yield mice with decreased glucose tolerance and increased blood glucose levels compared to lean-fed controls. Methicillin-resistant Staphylococcus aureus (MRSA) was inoculated in a surgical tibia fracture model to simulate open fracture, after which mice were treated with a combination of antibiotics and adjunctive teriparatide treatment. Radiographic union scale in tibia fracture (RUST) score was significantly poorer in diabetic mice compared to their lean non-diabetic counterparts. There were concomitant reductions in micro-computed tomography (μCT) parameters of callus architecture including bone volume/total volume, trabecular thickness, and total mineral density in T2DM mice. Biomechanical testing of fractured femora demonstrated diminished torsional rigidity, stiffness, and toughness to max torque.Adjuvant teriparatide treatment with systemic antibiotic therapy improved numerous parameters of bone microarchitecture bone volume, increased connectivity density, and increased trabecular number both in the lean and T2DM group. Despite the observation that T2DM mice showed significantly inferior fracture healing in-non-effected, which was further impaired by MRSA infection, adjuvant PTH administration significantly improved bone biomechanical strength compared to antibiotic treatment alone in infected T2DM fractures. Our results provide suggest that teriparatide may constitute a viable adjuvant therapeutic agent to improve bony union and bone microarchitecture to prevent the development of septic non-union under diabetic conditions.